Community pharmacy led atrial fibrillation detection and referral service – the Capture AF study. (25th November 2020) - Khanbhai, Z; Manning, S; Fordham, R; Xydopoulos, G; Grossi-Sampedro, C; Hussain, W
Abstract: Background: Atrial fibrillation (AF) is the most common sustained atrial arrhythmia. AF significantly affects patients' quality of life and increase morbidity and mortality. Patients with AF need to be appropriately anticoagulated to reduce the risk of stroke. Approximately every fifth stroke is due to AF and average costs for both health and social care is £44, 000 over the first five years. Recent updated guidelines on the management of AF have recommended that all patients over the age of 65 be offered screening in the community using either short term ECG or manual pulse palpation. Purpose: To determine the feasibility of an innovative community pharmacy led AF detection service incorporating referral for review and treatment to a specialist arrhythmia centre. Method: Community pharmacists received intensive training on AF, how to record an ECG using a Kardia monitor and documenting the consultation on a referral form hosted on a national pharmacy database called PharmOutcomes. Targeted opportunistic detection was undertaken by the pharmacists for anyone over the age of 65 years with risk factors for AF. Patients were referred by the pharmacist to the specialist team via PharmOutcomes if they had possible new AF, previous AF and not anticoagulated, anticoagulated but experiencing side effects or adherence issues or a high AF symptom burden. Patients initated on anticoagulation by the specialist team were referred back to the community pharmacist via the New Medicines Service (NMS) for adherence monitoring. Results: During a proof of concept phase (May to October 2016) and an upscale phase (May 2018-May 2019) 28 pharmacies were recruited and 1737 participants were enrolled in the study. 891 (51.3%) were male, 851 (41%) were aged over 75 years. 299 patients were referred by the pharmacists and 99 of these were seen by the specialist team in clinic. 28 patients (1.6%) were diagnosed with AF. 20 out of 28 (71.0%) were initiated on anticoagulation. 29 out of 146 patients (19.9%) had previous AF with either a high symptom burden (11) or a heart rate below 50 or above 100 beats per minutes (18). 7 patients (4.3%) with previous AF were started on anticoagulation. 48 out of 99 patients (48.4%) had their medication optimised. This included rate control titration and adjustment of anticoagulation doses. 31 out of 99 patients (31.3%) required further interventions such as holter monitors, echocardiograms or referral to other specialists. Conclusions: The results demonstrate that the this service is a robust multidisciplinary process for the detection, protection and perfection of AF. The direct referral pathway ensures that patients are reviewed by a specialist team and receive optimal treatment and management. Referral back to the community pharmacist via the NMS enhances concordance with anticoagulation. Further analysis is being undertaken to assess the cost-effectiveness and health impact of this service. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): The Health Foundation; ASHN in collaboration with BMS Pfizer